Penghancuran Estetika Kota: Bangunan Bersejarah di Kota Medan - Asmyta Surbakti (Mudra Jurnal Seni Budaya, 2008)
In the last two decades, specially when Medan City has got involved in the urban developmentalism, through the modernization and capital globalization, many historical buildings are destructed in order to build shopping centres, through hegemony and/or demolition by neglection. Using their hegemonic discourses, the local government supports controversially the destruction although the Perda was already issued. The most important discourse is the promise that the shopping centres will create employment for the local people as well as generate revenues for the government. To resist the destruction, counter-hegemonic ones are built by the society supported by critical groups, such as non-governmental organizations called Badan Warisan Sumatra (Sumatra Heritage Trust (BWS/SHT) with the central figure Hasti Tarekat as well as intellectuals, and mass media. Such a destruction does not only omit history and identity of the city but also neglect the tourism development based on the aesthetics of the heritages, which is potential to emansipatory praxis of the society.